Analisis Bibliometrik : Faktor Sanksi Perpajakan terhadap Kepatuhan Pembayaran Pajak bagi Wajib Pajak - Shinta Aliyah Putri; Wahyu Helmy Dimayanti Sukiswo (Journal Of Business, Finance, and Economics (JBFE), 2024)
This research can be used for topic mapping and further development of research directions related to "Tax Sanction Factors on Tax Payment Compliance for Taxpayers". For the author, this research also has the potential to obtain new keywords that will be used for further research topics. This study uses a bibliometric analysis method to review 200 scientific articles on related topics. Bibliometric analysis uses scientific article data obtained from Publish or Perish in the 2019-2024 period, then processed using the help of the VOSviewer application version 1.6.17. The results obtained from this study are that the topic related to tax sanctions on tax payment compliance is an interesting topic to study. There are several specific keywords that can be continued for further research such as the influence of tax understanding, tax quality, tax payers, and effects. It is hoped that this research can contribute to ideas for further research.